STRUKTUR TEKS DALAM PEMBERITAAN COVID PADA MEDIA MASSA ONLINE INSTAGRAM - Putriyanti, Lina (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
Covid-19 is a contagious disease caused by the SARS-CoV-2 virus, which is a type of coronavirus. The effects of this virus on the body include fever, dry cough, and difficulty breathing, which can lead to death. News about the COVID virus reappeared in May 2025 after several years of being dormant and declared over. This research aims to understand and describe the text structure in COVID news coverage on the online mass media Instagram @kompascom and @sindonews. Qualitative descriptive is a type of research utilizing the critical discourse analysis theory model by Teun A van Dijk, the first scheme being text (macro structure, superstructure, and micro structure) and discourse analysis approach. The data for this research consists of text excerpts from the Instagram accounts @kompascom and @narasinewsroom. The sources of the research data are the two Instagram accounts @kompascom and @narasinewsroom. The data collection technique involves listening and noting, and to verify the data's validity, data triangulation is required. Furthermore, to analyze the data, the Miles and Huberman interactive analysis technique is needed. The results of this study found the presence of a macro structure (theme about the increase of the COVID-19 virus), superstructure (introduction, content, and conclusion), and micro structure including semantics (meaning and presupposition), syntax (coherence and sentence structure), stylistics (lexicon), and rhetoric (graphic) in COVID-19 news on two Instagram social media accounts, @kompascom and @narasinewsroom.